2021
DOI: 10.14814/phy2.14987
|View full text |Cite
|
Sign up to set email alerts
|

Differential cardiotoxic electrocardiographic response to doxorubicin treatment in conscious versus anesthetized mice

Abstract: Introduction Doxorubicin (DOX), an anticancer drug used in chemotherapy, causes significant cardiotoxicity. This study aimed to investigate the effects of DOX on mouse cardiac electrophysiology, in conscious versus anesthetized state. Methods Male and female C57BL/6 mice were injected with saline, 20 or 30 mg/kg DOX. ECGs were recorded 5 days post‐injection in conscious and isoflurane anesthetized states. ECGs were analyzed using a custom MATLAB software to determine P, PR, QRS, QTc, and RR intervals as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…ECG is considered one of the sensitive tools that monitor this chemotherapy-induced cardiotoxicity [28]. Changes in the ECG parameters may be considered features that indicate the severity of dose-dependent adverse effects of DOX on the cardiac tissues [29]. Applications of machine learning as a type of artificial intelligence can be of great assistance to medical efficiency and diagnostic accuracy [30].…”
Section: Discussionmentioning
confidence: 99%
“…ECG is considered one of the sensitive tools that monitor this chemotherapy-induced cardiotoxicity [28]. Changes in the ECG parameters may be considered features that indicate the severity of dose-dependent adverse effects of DOX on the cardiac tissues [29]. Applications of machine learning as a type of artificial intelligence can be of great assistance to medical efficiency and diagnostic accuracy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Whether certain other anesthesia protocols may lead to less interference with murine cardiac EP remains elusive. However, available data on parameters such as hemodynamics and heart rate [34][35][36][53][54][55] suggest that all protocols have the potential to largely interfere with cardiac function and EP; therefore, further invasive studies are warranted to compare IF regimen with other isoflurane-based or injectable protocols, and identify the best compromise for invasive arrhythmia research in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…The study focused on pentobarbital, and a combination of ketamine, xylazine and acepromazine, which to our knowledge are both not commonly used in murine electrophysiological studies. Given that even studies assessing cardiac EP noninvasively have shown the fundamental impact of different narcosis regimens on ECG 35,36 and given the increasing importance of transgenic mouse models in arrythmia research, a systematic assessment of narcosis-related effects in general, and specifically of MMF and IF, on cardiac EP in mice is highly needed.…”
mentioning
confidence: 99%
“…This finding is in agreement with an earlier study that demonstrated a wider RR and QT interval in anesthetized versus conscious guinea pigs ( Hamlin et al, 2003 ). The effect of anesthesia on ECG parameters has been documented in other experimental models, including mice ( Warhol et al, 2021 ), as well as the impact of alternative anesthetic agents ( Ho et al, 2011 ). Similarly, clinical studies ( Kazanci et al, 2009 ) have also reported that anesthesia impacts ECG measurement values.…”
Section: Discussionmentioning
confidence: 99%